Zooplankton Dominance Shift in Response to Climate-Driven Salinity Change: A Mesocosm Study - Hall, Clio A. M.; Lewandowska, Aleksandra M. (Frontiers in Marine Science, 2022)
Climate change predictions indicate global changes in salinity with negative implications for plankton food webs; an important baseline for functioning of marine ecosystems. Current understanding of how salinity change will impact plankton communities is mostly limited to the salinization of freshwater environments, with little known about the effects of changing salinity in marine systems. In this study, we investigate the effect of salinity change on zooplankton communities under different salinity change scenarios of the Baltic Sea. Projections for future salinity change derived from regional physical-biogeochemical models were used to set-up an outdoor mesocosm experiment in the coastal area of the Gulf of Finland. Each mesocosm was inoculated with natural plankton using a mixture of both marine and freshwater communities, mimicking the natural influx of freshwater species from rivers into the Baltic Sea. Zooplankton diversity and composition changed possibly due to different salinity tolerances among the species. Among zooplankton, rotifers dominated in low salinities and cladocerans and copepods in high salinities. Our results suggest that the zooplankton community will shift to a rotifer dominated community in areas with declining salinity due to the intolerance of other zooplankton groups to freshening.